Joki Cilik Pacoa Jara: Berpacu Dalam Tradisi Dan Hukum Perlindungan Anak - Dian Rizky Rahmawati (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
Horse racing is a tradition that is still ongoing and is favored by the people of Sumbawa Island in general, one of which is the Bima community who knows this tradition as a jara pacoa which is ridden by children aged 5 (five) to 12 (twelve years), known as the little jockey. These young jockeys have become part of the ongoing tradition since before the regulation regarding the provisions of the age of children regulated in the law and is still undergoing the same tradition when the laws and regulations have regulated the provisions of the age of children and their rights and obligations in Indonesia. The study was conducted by doctrinal method with literature study. Writing data uses secondary data derived from written legal material, books and scientific work, which then the authors complete with observations, and interview results. The right of the community to maintain the tradition and its cultural values is protected by the law, as well as the rights of children, in the tradition of jara Pacoa can be a forum for children to excel, not exploited if the government makes regulations and more serious regulations both for protection of children and the Pacuan arena.